Money hard and soft on the international currency markets - Brown, Brendan (New York : Wiley, 1978)
The focus of this book is on the behaviour of transactors and the structure and operation of markets rather than on Grand Designs to "reform" the international monetary system. It provides an up-to-date explanation of international currency and Euro-markets. The most illuminating sections attempt to tackle the complex relations among spot markets, forward currency markets and the Euro-currency markets that have evolved in the past and to develop the analogy between money and commodity markets. Although many insightful passages shed light on how Euro-dollar markets differ from Euro-Sterling markets and Euro-Guilder markets, the exposition is occasionally not only terse. The author concluded that "a freely floating exchange rate system represents the latest stage reached of international monetary development" and that "it is inconceivable that the system will ever embrace all national monies"
"A Halsted Press book."
Includes bibliographical references: p. 175-176 and index.
usc 23/05/2018; 16/08/2018
Loans
Keywords: Foreign exchange; Money; Speculation; International finance